Pooled RT-qPCR testing for SARS-CoV-2 surveillance in schools - a cluster randomised trial. (September 2021) - Joachim, Alexander; Dewald, Felix; Suárez, Isabelle; Zemlin, Michael; Lang, Isabelle; Stutz, Regine; Marthaler, Anna; Bosse, Hans Martin; Lübke, Nadine; Münch, Juliane; Bernard, Marie-Annett; Jeltsch, Kathrin; et al.
Abstract: Background: The extent to which children and adolescents contribute to SARS-CoV-2 transmission remains not fully understood. Novel high-capacity testing methods may provide real-time epidemiological data in educational settings helping to establish a rational approach to prevent and minimize SARS-CoV-2 transmission. We investigated whether pooling of samples for SARS-CoV-2 detection by RT-qPCR is a sensitive and feasible high-capacity diagnostic strategy for surveillance of SARS-CoV-2 infections in schools. Methods: In this study, students and school staff of 14 educational facilities in Germany were tested sequentially between November 9 and December 23, 2020, two or three times per week for at least three consecutive weeks. Participants were randomized for evaluation of two different age adjusted swab sampling methods (oropharyngeal swabs or buccal swabs compared to saliva swabs using a 'lolli method'). Swabs were collected and pooled for SARS-CoV-2 RT-qPCR. Individuals of positive pooled tests were retested by RT-qPCR the same or the following day. Positive individuals were quarantined while the SARS-CoV-2 negative individuals remained in class with continued pooled RT-qPCR surveillance. The study is registered with the German Clinical Trials register (registration number: DRKS00023911). Findings: 5, 537 individuals were eligible and 3970 participants were enroled and included in the analysis. In students, a total of 21, 978 swabs were taken and combined in 2218 pooled RT-qPCR tests. We detected 41 positive pooled tests (1·8%) leading to 36 SARS-CoV-2 cases among students which could be identified by individual re-testing. The cumulative 3-week incidence for primary schools was 564/100, 000 (6/1064, additionally 1 infection detected in week 4) and 1249/100, 000 (29/2322) for secondary schools. In secondary schools, there was no difference in the number of SARS-CoV-2 positive students identified from pooled oropharyngeal swabs compared to those identified from pooled saliva samples (lolli method) (14 vs. 15 cases; 1·3% vs. 1·3%; OR 1.1; 95%-CI 0·5–2·5). A single secondary school accounted for 17 of 36 cases (47%) indicating a high burden of asymptomatic prevalent SARS-CoV-2 cases in the respective school and community. Interpretation: In educational settings, SARS-CoV-2 screening by RT-qPCR-based pooled testing with easily obtainable saliva samples is a feasible method to detect incident cases and observe transmission dynamics. Funding: Federal Ministry of education and research (BMBF; Project B-FAST in "NaFoUniMedCovid19"; registration number: 01KX2021).